Kajian Permintaan Perjalanan Penumpang dalam Rangka Penyediaan Prasarana Sarana Transportasi Umum di Bali - Hermawati, Putu; Aryawan, I G M Oka; Sutapa, I Ketut; Santiana, I Made Anom (Badan Riset dan Inovasi Daerah Provinsi Bali, 2020)
Purpose: To develop a more comprehensive transportation policy in Bali, this research needs to be conducted. Research methods: Data collection is done by conducting questionnaire-based surveys. Findings: The internal distribution trips shows the highest trip production from Denpasar and Kuta, about 24.93% and 11.75%, while the largest trip attraction are also to Denpasar and Kuta, which are 13.76% and 16.73% of the total number of people trips per day. The distribution of external trips shows that most people going in and out of Bali are through Ngurah Rai Airport and Gilimanuk Port. The modal selection shows that the most used are 85.40% motorcycle, 10.27% car, 3.60% trucks and 0.73% public transportation. The forecasts of trip generation and attraction have growth rates of 5.812%/year. Implications: It needs anticipated to develop new alternative modes based on technology from Denpasar to all districts, such as Train/LRT/ART and ferry transportation, which was agreed by 83.56% and 89.33% of the people.